1998
DOI: 10.1590/s0100-879x1998000600012
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and postnatal depression among low income Brazilian women

Abstract: Postnatal depression is a significant problem affecting 10-15% of mothers in many countries and has been the subject of an increasing number of publications. Prenatal depression has been studied less. The aims of the present investigation were: 1) to obtain information on the prevalence of prenatal and postnatal depression in low income Brazilian women by using an instrument already employed in several countries, i.e., the Edinburgh Postnatal Depression Scale (EPDS); 2) to evaluate the risk factors involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
7
58

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(145 citation statements)
references
References 14 publications
6
74
7
58
Order By: Relevance
“…A prevalência de DPP encontrada foi similar a outros trabalhos 15,16 , sendo elevada, considerando-se a média da literatura entre 10 e 20%. Sobre o TDPM, existem escassos trabalhos 5 evidenciando a sua relação com a depressão, porém é assunto discutível.…”
Section: Discussionunclassified
“…A prevalência de DPP encontrada foi similar a outros trabalhos 15,16 , sendo elevada, considerando-se a média da literatura entre 10 e 20%. Sobre o TDPM, existem escassos trabalhos 5 evidenciando a sua relação com a depressão, porém é assunto discutível.…”
Section: Discussionunclassified
“…Thus, prevalence rates of depression during pregnancy were significantly higher in low-income countries. The main risk factors associated with these differences are past history of psychiatric disorders, poor antenatal care, poor nutrition, stressful life events, economic deprivation and gender based violence, which are more prevalent in developing countries 4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…These studies, except for an outlier 13 (i.e. a study that reported an antenatal depression prevalence of 37.9%) reported prevalence rates ranging from 13% to 20.8% 4,7,12,14,26,29,37 .…”
Section: Introductionmentioning
confidence: 99%
“…Dez estudos estimaram a prevalência da DPP no Brasil 22,[29][30][31][32][33][34][35][36][37] . Foram encontradas taxas de 7,2% a 43%.…”
Section: Depressão Pós-parto (Dpp)unclassified